1991
DOI: 10.1136/hrt.66.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of tolerance and lack of rebound with intermittent dose titrated transdermal glyceryl trinitrate. The Transdermal Nitrate Investigators.

Abstract: Objectives-To investigate the efficacy of transdermal glyceryl trinitrate given continuously and with a nocturnal nitrate free period.Design-Double blind placebo controlled study with two parallel limbs.Setting-Multicentre trial.Patients-52 patients randomised to receive either continuous treatment (23 patients) or intermittent treatment with an individually titrated dose (29 patients) for 14 days: both treatments were compared with placebo in a crossover fashion.Intervention-Continuous treatment with 10 mg pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Also, Demots and Glasser observed that intermittent therapy caused a so-called zero-hour effect, apparent as a reduced exercise capacity (compared with placebo-treated patients) at the time just before the daily patch application [15]. Other studies, however, have not been able to demonstrate increased angina frequency during the patch-off hours [34,43,45,46], and in the new large intermittent transdermal nitroglycerin study by Parker et al, a significant zero-hour effect could not be demonstrated [43]. A recent study indicates that a rebound effect with reduced exercise tolerance is most prominent 2-6 hours after patch removal [47], and the problem may hence be underestimated in studies testing just before renewed application, that is, 12 hours after removal.…”
Section: Harmful Effects In the Nitrate-free Periods?mentioning
confidence: 99%
“…Also, Demots and Glasser observed that intermittent therapy caused a so-called zero-hour effect, apparent as a reduced exercise capacity (compared with placebo-treated patients) at the time just before the daily patch application [15]. Other studies, however, have not been able to demonstrate increased angina frequency during the patch-off hours [34,43,45,46], and in the new large intermittent transdermal nitroglycerin study by Parker et al, a significant zero-hour effect could not be demonstrated [43]. A recent study indicates that a rebound effect with reduced exercise tolerance is most prominent 2-6 hours after patch removal [47], and the problem may hence be underestimated in studies testing just before renewed application, that is, 12 hours after removal.…”
Section: Harmful Effects In the Nitrate-free Periods?mentioning
confidence: 99%
“…The best currently available estimate for the incidence of rebound with intermittent patch therapy, based on the published data in randomised studies totalling over 500 patients, suggests that rebound angina may occur in 2-4% of patients. Reassuringly, there is no evidence for any exacerbation of silent ischaemia during overnight patch withdrawal (Fox et al, 1991).…”
Section: Intermittent Therapy-potential Disadvantagesmentioning
confidence: 99%
“…Although continuous therapy may be of some value, benefits are substantially less than during intermittent therapy. Numerous studies, totalling over 500 randomised patients, have demonstrated the benefits of intermittent patch therapy over continuous (Cowan et al, 1987;De Milliano et al, 1989;DeMots & Glasser, 1989;Fox et al, 1991;Luke et al, 1987;Scardi et al, 1991;Schaer et al, 1988). For this reason, where possible, intermittent therapy is preferable to continuous.…”
Section: The Role Of Intermittent Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Intermittent nitrate therapy increases exercise duration and maintains anti-ischemic effects, without significant evidence of nitrate tolerance or rebound phenomenon (17,(49)(50)(51)(52). Although intermittent nitrate therapy has proved superior to continuous therapy, intermittent therapy may be associated with rebound myocardial ischemia during the nitrate-free period.…”
Section: Benefits Of Eccentric Dosing Of Nitratesmentioning
confidence: 99%